Pre-eclampsia and platelet indices: a cross sectional study - Khan, Javid Ahmed; Ashraf, Aadil; Qureshi, Waseem; Fayaz, Faizana (International Journal of Research in Medical Sciences, 2022)
Background: Pre-eclampsia is a complex disease process originating at the maternal- fetal interface that affects multiple organ systems. The exact pathophysiology of preeclampsia is not known but it is considered to be associated with endothelial cell dysfunction, increased inflammatory responses and hypercoagulability. The receptors located on platelets are activated in pre-eclampsia by several proteases plus the vasoconstriction associated with preeclampsia leads to platelet activation which can be evaluated by platelet indices like platelet count, mean platelet volume (MPV), platelet distribution width (PDW) and palteletcrit (PCT). The objective of this study was to compare the platelet count and platelet indices- MPV, PDW, and PCT in patients with pre-eclampsia and normotensive pregnant women. Methods: A cross sectional study which included a total of 204 patients divided into two groups (102 pre-eclampsia and 102 control. The patients were compared for platelet count and platelet indices like MPV, PDW and PCT. Results: The platelet count (PC) was decreased in pre-eclampsia group as compared to control group with statistically significant difference in means between the two groups (p<0.05). The MPV and PDW also showed significant difference between the two groups (p<0.05) with preeclampsia group having increased MPV and PDW values. The PCT value was lower in pre-eclampsia group as compared to control group but it did not reach statistically significant level. Conclusions: In pre-eclampsia patients while as MPV and PDW showed increased value as compared to control group and the difference between the two had statistical significance, platelet count was lower in them and had statistical significance when compared to control group. Therefore these platelet indices and platelet count can be used to predict and prevent complications arising from preeclampsia.